2020
DOI: 10.1002/ppul.24960
|View full text |Cite
|
Sign up to set email alerts
|

l‐Citrulline treatment alters the structure of the pulmonary circulation in hypoxic newborn pigs

Abstract: Background Dysregulated nitric oxide (NO) signaling contributes to chronic hypoxia (CH)‐induced pulmonary hypertension (PH). NO signaling is improved and pulmonary vascular resistance (PVR) is reduced in CH piglets treated with the l‐arginine‐NO precursor, l‐citrulline. We hypothesized that l‐citrulline might cause structural changes in the pulmonary circulation that would contribute to the reduction in PVR and that the l‐citrulline‐induced structural changes would be accompanied by alterations in vascular end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…Studies with animal models have also demonstrated that treatment with either sildenafil or L-citrulline can have a beneficial impact on the pulmonary circulation and lungs that extends beyond that of a pulmonary vasodilator. L-citrulline treatment reduced pulmonary vascular wall thickness and increased lung capillary formation in a newborn piglet model of chronic hypoxia-induced PH [166]. Alveolar and vascular growth were preserved [167,168], and pulmonary arterial wall thickness and right ventricular wall hypertrophy were reduced by L-citrulline treatment in a hyperoxic newborn rat model of BPD-PH [168].…”
Section: Additional Comments About Rcts Manipulating No Signalingmentioning
confidence: 96%
“…Studies with animal models have also demonstrated that treatment with either sildenafil or L-citrulline can have a beneficial impact on the pulmonary circulation and lungs that extends beyond that of a pulmonary vasodilator. L-citrulline treatment reduced pulmonary vascular wall thickness and increased lung capillary formation in a newborn piglet model of chronic hypoxia-induced PH [166]. Alveolar and vascular growth were preserved [167,168], and pulmonary arterial wall thickness and right ventricular wall hypertrophy were reduced by L-citrulline treatment in a hyperoxic newborn rat model of BPD-PH [168].…”
Section: Additional Comments About Rcts Manipulating No Signalingmentioning
confidence: 96%